Análise da dinâmica do programa de aquisição de alimentos no município de Mirante do Paranapanema/SP - Pereira, Elizabeth Lima (2016)
The National Program for the Strengthening of Family Agriculture (PRONAF) emerges as a tool to build a new model of rural development in the country, whose main mission is to combat the inequalities that have traditionally marked the state policies aimed at stimulating a change in the technical basis of agriculture. That his institution marks the recognition of family farmers as a social category and opens the way for the implementation of a series of public policies aimed at attending to the world of family agriculture. Among these, the Food Acquisition Program (PAA) was created in 2003 with the purpose of promoting food and nutritional security, linked to the strengthening of family farming. The purpose of this research was to analyze PRONAF, in the period 1999-2012, regarding the distribution and coverage of resources and also to analyze the PAA, in the period of 2011-2014, in the region of Pontal do Paranapanema / SP, with emphasis in the municipality of Lookout. In addition to bibliographical and documentary research, the work used data from the Central Bank of Brazil in the case of PRONAF and the SAGI Platform in the PAA case. In addition, semi-structured interviews were conducted with farmers' organizations, and members of municipal PAA management, as well as application form with farmers providing food in the program. It was verified that, the resources of the PRONAF are strongly significant in few municipalities, highlighting concentration of resources. In the case of the PAA, it has been found that it has contributed to farmers' activities in agriculture, not just in livestock activities, but also before the program. It also influences better feeding of the farmers involved, as well as the families that receive the food purchased by the PAA in the municipality. A sensitive alteration of the productive matrix was observed. The program also made possible, even in a timely manner, investments in productive activities